Pemodelan Berdasarkan Penerapan Value Engineering Untuk Efisiensi Biaya Pada Proyek Jalan Di Kota Manado - Rumpesak, Norio H; Mandagi, Robert J. M.; Jansen, Freddy (JURNAL ILMIAH MEDIA ENGINEERING, 2017)
One of the alternative methods in the effort to save budget cost in order to achieve the purpose of optimizing the regional development budget by applying Value Engineering in the planning of road improvement project. Because until now the application of VE method has never been done on road improvement project then of course this is an interesting thing to be studied. The road construction project consists of 10 (ten) work divisions, and for road improvement projects in Manado, the total cost is dominated by 3 (three) divisions: Division II: Drainage, Division V: Gilded Pile, and Division VI: Asphalt. By using regression method for various budget cost plan of road improvement project in Manado that has been through the process of appraisal using value engineering hence can be determined model which will represent the planning of budget project of road improvement in Manado. Based on the results of the analysis that has been done in the previous chapter, the equations of the estimated cost estimation model of road project in Manado city are: D5 = 722.035,135 (LPA) +813.598,967 (LPB) + 23.147,235 (ACWC) + 3.197.478,172 ; D5 + D6 = 182.681,383 (LPA) + 1.103.240,694 (LPB) + 2.395.243,112 (ACWC) - 35.405.642,200; D6 = -539.353,751 (LPA) + 289,641,726 (LPB) + 2,372,095,877 (ACWC) - 38,603,120,400; TotalBiaya = 779,595,726 (LPA) + 1,502,980,050 (LPB) + 2,381,140,834 (ACWC) - 57,391,692,800; D2 + D5 + D6 = 498.018,081 (LPA) + 920.192,655 (LPB) +2.248.914,833 (ACWC) +97.002.258,560.Keywords—Value Engineering, Construction Project, Road Improvement